Private life in New Kingdom Egypt - Meskell, Lynn (Princeton University Press, 2005)
This work examines how ordinary ancient Egyptians lived their lives. The aim of this book is to give a new insight on how life may have been experienced and conceived of by ancient Egyptians in all thier variety.